THE INFLUENCE OF COMPUTER ANXIETY AND COMPUTER ATTITUDE TO THE END USER COMPUTING SKILL ( Study on Perum Perhutani Unit II KPH Pasuruan, Malang) - Mardan Indra Lukmana (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
The result can be seen that computer anxiety in fear variable didn’t significantly influence to the end user computing skill at PSDH (Pengolahan Sumber Daya hutan) in the Perum Perhutani unit II KPH Pasuruan, Malang, with a significance level is 0,439>0,05 and anticipation variable contained in computer anxiety has a influence significantly to the end user computing with a significance level is 0,018<0,05. Pessimism variable contained in Computer attitudes didn’t has influence significantly, with significance level is 0,427>0,05. and Optimism variable didn’t has influence significantly with significance level 0,206>0,05. While determining the coefficient for 0,248 which means that 24,8% use the computer skill are influenced by computer anxiety (Fear and Anticipation variable) and Computer Attitude (Pessimism and Optimism Variable), The remaining 75,2% is determined by other factors. Keyword: Computer Anxiety, Computer Attitude, End User Computing Skill